ICT as didactic tools for physical education teachers in formal education through Flipped Classroom Model - Espejo García, R.; Infantes Rojas, B.; Moya Medina, M.A.; Morente-Oria, H. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
ICTs are tools present in our life’s areas, the rise of which has led to their introduction in the educational curriculum and in teaching as a key and indispensable part of it. Thanks to scientific advancement, performance measurement devices are becoming more frequent and easy to use by professionals in physical activity and sports. Therefore, the present work aims to make a didactic proposal based on the use of ICT as a methodological strategy and tool for assessing and implementing training programs within the curricular framework of the educational stage Professional Training of the Higher Technician in Physical Conditioning. This proposal will consist of seven sessions for the subject of "Assessment of the physical condition and intervention in accidents" where they will handle digital tools that favor developing their objectives and skills and integration into the professional market.